Pediatric Cardiac Surgery in Low-and Middle-Income Countries: Present Status and Need for a Paradigm Shift - Murala, John S. K.; Karl, Tom R.; Pezzella, A. Thomas (Frontiers in Pediatrics, 2019)
In low and mid-income countries, there has been a 50% global decrease in the incidence of preventable deaths of children since 1990. However, the mortality from non-communicable diseases such as congenital heart disease (CHD) has not changed. Of the estimated 1.3 million children born yearly, over 90% do not have access to cardiac care. With the increasing fertility rates in sub-Saharan Africa, the health burden of CHD will increase as well. Over the last 30 years much has been achieved with short term cardiac medical missions. However, much remains to be done to provide long term solutions needed to achieve the sustainable development goal of reducing deaths of children less than 5 years of age. This review discusses the present status and the need for a paradigm shift to achieve long term sustainability.